Effect of some humic substances on iron availability in some calcareous soils from Homs governorate (Journal of Hama University, 2022)
An incubation experiment was carried out in order to study the effect of adding some humic substances (fulvic acids, humic acids and commercial humax) according to the rates (0-500-1000-2000 mg.kg-1) for each of them on the bioavailability of iron in three soils contain different amount of total carbonate. The results showed a significant improvement in the availability of iron when adding all the humic substances, as the available iron concentration increased significantly (LSD0.05) when adding fulvic acids compared to the control in the three studied soils.It was also found that there was a negative significant correlation between the total carbonate content of the studied soil and its available iron content. When comparing the studied humic substances with regard to the effect on the available iron content in the soil, it was noted that the fulvic acid treatment was superior to the humax treatment, which in turn was superior to the humic acid treatment.